Can numerical modeling help understand the fate of tau protein in the axon terminal?. Issue 2 (25th January 2016) - Kuznetsov, I.A.; Kuznetsov, A.V.
Abstract : In this paper, we used mathematical modeling to investigate the fate of tau protein in the axon terminal. We developed a comprehensive model of tau transport that accounts for transport of cytosolic tau by diffusion, diffusion transport of microtubule (MT)-bound tau along the MT lattice, active motor-driven transport of MT-bound tau via slow axonal transport mechanism, and degradation of tau in the axon due to tau's finite half-life. We investigated the effect of different assumptions concerning the fate of tau in the terminal on steady-state transport of tau in the axon. In particular, we studied two possible scenarios: (i) tau is destroyed in the terminal and (ii) there is no tau destruction in the terminal, and to avoid tau accumulation we postulated zero flux of tau at the terminal. We found that the tau concentration and percentage of MT-bound tau are not very sensitive to the assumption concerning the fate of tau in the terminal, but the tau's flux and average velocity of tau transport are very sensitive to this assumption. This suggests that measuring the velocity of tau transport and comparing it with the results of mathematical modeling for different assumptions concerning tau's fate in the terminal can provide information concerning what happens to tau in the terminal.